Mengoptimalkan Pelvic Rocking menggunakan gym ball untuk menurunkan Low back Pain Pada kehamilan - Ermasari, Anissa; Rudi Winarno (Poltekkes Kemenkes Tanjung Karang, 2024)
Low Back Pain (LBP) is discomfort due to physiological changes during pregnancy that will have an impact on the quality of life of pregnant women, such as decreased physical mobility, reduced sleep quality, and increased psychological stress. The high prevalence of LBP in pregnancy ranges from 24% to 90%. Therefore, it is necessary to strive for pain management that is easy to do, has minimal side effects for pregnancy, and can be done independently by pregnant women, with minimal equipment and low costs. Using a gym ball in pelvic rocking exercises can stretch the pelvic muscles and increase levels of the beta-endorphin hormone, which can reduce pain. This study aims to analyze using a gym ball in pelvic rocking exercises to minimize the pain scale of low back pain in pregnancy. This research design is a quasi-experiment with a Pre-test, Post-test, and Nonequivalent Control Group Design. The sampling technique in this research was Purposive sampling, with 30 respondents divided into two groups. The instrument used was the Visual Analog Scale (VAS) to assess the level of the LBP pain scale. Data analysis used the t-test. The results of statistical tests show a p-value of 0.000 (p-value<0.05), so it can be concluded that using a gym ball in pelvic rocking exercises affects the LBP scale in pregnancy.